Workshop Pengenalan Green Chemistry - Nada Setiyani; Irhamni Rosyadi; Anjeli Carolina; Putri Rifa Wahyu Setyowati; Ria Rismaya; Riri Setyani (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Green chemistry generally includes effective concepts and approaches to prevent environmental pollution caused by toxic and hazardous processes and chemicals. In chemistry practicum activities, it is expected to prevent chemical pollution by trying to use green chemistry principles to reduce, eliminate and even replace the use of toxic and hazardous chemicals. This workshop aims to socialize green chemistry as a way to reduce environmental pollution levels and the volume of chemical waste during practicum with resource persons, namely PLP students of Sultan Ageng Tirtayasa University and collaborating with coaches and heads of extracurricular Youth Scientific Groups (KIR).